Mewujudkan Peserta Didik Terampil dan Mandiri Melalui Kewirausahaan di Sekolah Satu Atap - Siti Nurchayati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
The One Roof School is the Government's innovation in the compulsory education program in Remote, Scattered, and Isolated areas. One of the programs to create skilled and independent students is the entrepreneurship program. This research is field research with a case study method taken from the best experience conducted by school principals. This research was conducted at the Tambelang One Roof Public Junior High School, Bekasi, West Java for the 2019/2020 academic year. During implementation, students are observed and measured using an instrument sheet, this aims to measure the skilled and independent attitudes of students. Data were analyzed using the Miles and Huberman interactive analysis method. Based on the results of data analysis in the field, it was found that after the implementation of the program, the number of students who were quite skilled to very skilled became 98% or as many as 63 children, with an increase of 86%. Independence increased to 95%, from only 3 people to as many as 64 people. In conclusion, through the direct practice of business activities in schools, students can experience, examine, and understand the concept of entrepreneurship so as to shape students' entrepreneurial attitudes and mentality, namely being skilled and independent.